Could the Interaction between Arbuscular Mycorrhizal Fungi and Biostimulants Improve the Plant Physiological Status of Prosopis alba Seedlings? - Santacruz-García, Ana Carolina; Gomez, Adriana Teresita; Senilliani, Maria Gracia; Guzmán, Analía del Valle; Sagadin, Monica Beatriz; Ewens, Mauricio; Frías, Rodrigo Sebastián; Coria, Cristian; Gómez, Joaquín; Nazareno, Mónica Azucena (MDPI, 2022)
Presentado al 3rd International Electronic Conference on Forests—Exploring New Discoveries and New Directions in Forests, 15–31 October 2022